Elderly, sexually transmitted infections and aids: knowledge and risk perception - Brito, Nívea Maria Izidro de (2016)
Introduction: In the context of chronic diseases, aids pandemic has generated discussions at the international level on methods to control its progress, including in the elderly population, which presents significant incidence of cases. Objective: To investigate the knowledge and verify the perception of risk among the elderly individuals concerning contamination by Sexually Transmitted Infections (STI) and HIV. Methods: This is a quantitative descriptive study, which was conducted with 55 elderly who are participants of groups in two family health units that are interconnected to a school network. Results: Most of the elderly was aged between 60–70 years, male, married, catholic, and with incomplete elementary educational level. Additionally, 40% of the elderly reported the use of condoms as a primary method of prevention of sexually transmitted infections, 21.9% of them answered that HIV is sexually transmitted from one person to another by means of sexual contact, and 38.2% mentioned that disease has no cure. On the perception of risk, 76.4% reported that they had no possibility of acquiring sexually transmitted infections or HIV. This factor may contribute to a misperception of this population of being less vulnerable and to the unawareness about the risks, making them susceptible to the infection, which may also increase the rate of elderly individuals infected on the national scene. Conclusion: Government and nongovernmental organizations should invest in educational practices that enable the insertion of the elderly in a context to address sexuality, providing protection and quality of life for our citizens.